Efeitos do tratamento tópico com o látex da Euphorbia tirucalli na sobrevida de ratos com peritonite experimental - Araújo, Lilhian Alves de (2013)
The use of plants of the family Euphorbiaceae, particularly Euphorbia tirucalli has been popularly widespread for treating a variety of diseases of infectious, tumoral, and inflammatory. Considering the popular use of E. tirucalli in the treatment of diseases and research demonstrating antimicrobial and immunomodulating effects, this study evaluated the effect of peritoneal lavage with the aqueous latex E. tirucalli on the survival of rats with fecal experimental peritonitis. For this purpose, fecal peritonitis was induced in 24 Wistar rats and were divided randomly into four groups of six animals, as follow: 1- control, no treatment; 2- treatment with a single dose of intramuscular Unasyn (antibiotic) 30mg, 3- wash the abdominal cavity with saline solution 0.9%; 4- wash the abdominal cavity with E. tirucalli concentration of 12mg/mL. Animals that died were necropsied and the time of death noted. The survivors were mercy killing on the 11th postoperative and later necropsy was performed. The results showed that the groups 1 and 3, 1 and 4, 2 and 3; 2 and 4 exhibited significant differences (p <0.01) in relation to hours of life. The treatment with the washing of saline solution and the E. tirucalli has made surviving the animals for the same period, no deaths in the group treated with latex in the period.